ANALISIS IMPLEMENTASI BUDAYA ADAPTIF PUSKESMAS TEGALLALANG II KABUPATEN GIANYAR DALAM PROGRAM PENGENTASAN STUNTING PADA MASA PANDEMI COVID-19 - Ni Kadek Esilia Septigar Pranati; Pande Putu Januraga (ARCHIVE OF COMMUNITY HEALTH, 2022)
The stunting alleviation program is a national priority during the COVID-19 pandemic, thus encouraging primary health center to adapt. It is necessary to conduct research to determine the implementation of the adaptive culture of the Tegallalang II Primary Health Center in Gianyar Regency in the stunting alleviation program during the COVID-19 pandemic through the dimensions of creating change, customer focus, and organizational learning. The design of this research is descriptive with qualitative methods. The research informants were 16 people from health workers in the working area of ??the Tegallalang II Primary Health Center who were selected through purposive sampling technique. The data collection instrument used in-depth interview guidelines. The results showed that the Tegallalang II Primary Health Center had the main quality of customer-centered cultural adaptive culture. Change depends on the organization and the individual. The unpreparedness of health human resources is a major factor in the barriers to change. The lack of knowledge sharing activities causes the organizational level learning aspect to be less active. Internal and external support from health center is needed to increase the quantity of human resources and improve organizational learning. Key words: Adaptive Culture, Primary Health Center, Stunting Alleviation Program, COVID-19 Pandemic